Undoped ruthenium oxide as a stable catalyst for the acidic oxygen evolution reaction - Jiayi Tang; Daqin Guan; Hengyue Xu; Leqi Zhao; Ushtar Arshad; Zijun Fang; Tianjiu Zhu; Manjin Kim; Chi-Wen Pao; Zhiwei Hu; Junjie Ge; Zongping Shao (Nature Communications)
Abstract Reducing green hydrogen production cost is critical for its widespread application. Proton-exchange-membrane water electrolyzers are among the most promising technologies, and significant research has been focused on developing more active, durable, and cost-effective catalysts to replace expensive iridium in the anode. Ruthenium oxide is a leading alternative while its stability is inadequate. While considerable progress has been made in designing doped Ru oxides and composites to improve stability, the uncertainty in true failure mechanism in acidic oxygen evolution reaction inhibits their further optimization. This study reveals that proton participation capability within Ru oxides is a critical factor contributing to their instability, which can induce catalyst pulverization and the collapse of the electrode structure. By restricting proton participation in the bulk phase and stabilizing the reaction interface, we demonstrate that the stability of Ru-oxide anodes can be notably improved, even under a high current density of 4 A cm‒2 for over 100 h. This work provides some insights into designing Ru oxide-based catalysts and anodes for practical water electrolyzer applications.